Effect of channel miniaturization on entropy generation in hybrid corrugation configuration channel. (December 2022) - Kumar, Krishan; Kumar, Rajan; Bharj, Rabinder Singh
Abstract: The entropy generation in the novel hybrid inward trapezoidal-outward triangular corrugated channel is analyzed numerically. The corrugated channel diameter is miniaturized with a corresponding rise in the number of channels. The corrugation parameters are also varied corresponding to the channel diameter and total heat is considered constant. The temperature of the water at the channel inlet is 300 K, along with the constant total mass flow rate corresponding to the four Reynold numbers. This study investigates the influence of Reynold number and channel dimension downsizing on entropy generation owing to fluid friction and heat transfer. The miniaturization of channel diameter and enhancement in the Reynold number reduces the irreversibility due to heat transfer and augments the irreversibility due to flow friction. The change in the total entropy generation with a change in Reynold number and channel diameter is found dependent upon the magnitude of frictional and heat transfer entropy generation. The optimum Reynold number and an optimum number of channels (or optimum diameter) are obtained corresponding to the least entropy generation. At the highest Reynold number, case N2 resulted in the least entropy generation, whereas overall lowest entropy generation is found in the N4 case at the lowest Reynolds number. The comparison of the corrugated channel with the simple channel is done using augmentation entropy generation number and corrugated channels are found beneficial at lower Reynold numbers over the simple channels. Highlights: Numerically assessed the effect of corrugated channel miniaturization on S gen . The inward trapezoidal-outward triangular hybrid corrugated channel is used. The rise in the Re reduces S gen, HT and enhances S gen, FR . Optimum Re and an optimum number of channels exist corresponding to the least S gen . Corrugated channel dimension miniaturization reduces S gen, HT and augments S gen, FR .